Thoughts on Social Design - Trockel, Walter; Haake, Claus-Jochen (Studies in Economic Design)
One of the fundamental problems in applications of methods and results from mechanism design and implementation theory is the effective enforcement of theoretically established equilibria by which social choice rules are implemented. Hurwicz (2008) and Myerson (2009) introduce different concepts of formalizing enforcement of institutional rules via the introduction of legal and illegal games. In this note the relation of their concepts with that of a social system defined inDebreu (1952) is analyzed and its potential of being instrumental for modelling institution design is discussed. The existence proof for such a system, also known as generalized game or abstract economy had been the basis for the existence proof of a competitive equilibrium of an economy.

The Influence of Bribery and Relative Reciprocity on a Physician's Prescription Decision - An Experiment - Hilleringmann, Vanessa
Focusing on a physician's relationship to a briber and a patient, this experiment analyzes the influence of a bribe on a physician's treatment decision. We conduct a partner treatment, in which briber and physician play together for the whole experiment and a stranger treament, where briber and physician are re-matched every period. With the help of the two treatments, we vary the relative reciprocity between the physician and the two other actors, briber and patient. Additionally we use a follow up questionnaire to measure the behavioral motivation of the participants. We find that reciprocity leads to bribery relationships: In the partner treatment physicians act corruptly more often. Just the variation of the relative reciprocity between the treatments shows differences in the behavior of the subjects. Differences in the participants' preferences deliver no explanation for their behavior in our experiment.
Keywords: Corruption; Reciprocity; Physician-Patient Relationship

Bloom Filter Encryption and Applications to Efficient Forward-Secret 0-RTT Key Exchange - Derler, David; Jager, Tibor; Slamanig, Daniel; Striecks, Christoph (Advances in Cryptology - EUROCRYPT 2018 - 37th Annual International Conference on the Theory and Applications of Cryptographic Techniques, Tel Aviv, Israel, April 29 - May 3, 2018 Proceedings, Part III)

JASPER: Joint Optimization of Scaling, Placement, and Routing of Virtual Network Services - Dräxler, Sevil; Karl, Holger; Mann, Zoltan Adam (IEEE Transactions on Network and Service Management)
To adapt to continuously changing workloads in networks, components of the running network services may need to be replicated (scaling the network service) and allocated to physical resources (placement) dynamically, also necessitating dynamic re-routing of flows between service components. In this paper, we propose JASPER, a fully automated approach to jointly optimizing scaling, placement, and routing for complex network services, consisting of multiple (virtualized) components. JASPER handles multiple network services that share the same substrate network; services can be dynamically added or removed and dynamic workload changes are handled. Our approach lets service designers specify their services on a high level of abstraction using service templates. JASPER automatically makes scaling, placement and routing decisions, enabling quick reaction to changes. We formalize the problem, analyze its complexity, and develop two algorithms to solve it. Extensive empirical results show the applicability and effectiveness of the proposed approach.

Causal Linearizability: Compositionality for Partially Ordered Executions - Doherty, Simon; Derrick, John; Dongol, Brijesh; Wehrheim, Heike (CoRR)

Die Bedeutung von Kunststoffen für hybride Leichtbaustrukturen - Moritzer, Elmar; Landgräber, B. (Wissenschaft im Angesicht großer gesellschaftlicher Herausforderungen)

Effect of Dietary Sugar Intake on Biomarkers of Subclinical Inflammation: A Systematic Review and Meta-Analysis of Intervention Studies - Della Corte, Karen; Perrar, Ines; Penczynski, Katharina; Schwingshackl, Lukas; Herder, Christian; Buyken, Anette (Nutrients)

The relevance of restrained eating behavior for circadian eating patterns in adolescents - Koch, Stefanie A. J.; Alexy, Ute; Diederichs, Tanja; Buyken, Anette; Roßbach, Sarah (PLOS ONE)

Dietary Patterns in Primary School are of Prospective Relevance for the Development of Body Composition in Two German Pediatric Populations - Wolters, Maike; Joslowski, Gesa; Plachta-Danielzik, Sandra; Standl, Marie; Müller, Manfred; Ahrens, Wolfgang; Buyken, Anette (Nutrients)
This study performed comparative analyses in two pediatric cohorts to identify dietary patterns during primary school years and examined their relevance to body composition development. Nutritional and anthropometric data at the beginning of primary school and two or four years later were available from 298 and 372 participants of IDEFICS-Germany (Identification and prevention of Dietary-induced and lifestyle-induced health Effects In Children and infants Study) and the KOPS (Kiel Obesity Prevention Study) cohort, respectively. Principal component analyses (PCA) and reduced rank regression (RRR) were used to identify dietary patterns at baseline and patterns of change in food group intake during primary school years. RRR extracted patterns explaining variations in changes in body mass index (BMI), fat mass index (FMI), and waist-to-height-ratio (WtHR). Associations between pattern adherence and excess gain in BMI, FMI, or WtHR (>75th percentile) during primary school years were examined using logistic regression. Among PCA patterns, only a change towards a more Mediterranean food choice during primary school years were associated with a favorable body composition development in IDEFICS-Germany (p < 0.05). In KOPS, RRR patterns characterized by a frequent consumption of fast foods or starchy carbohydrate foods were consistently associated with an excess gain in BMI and WtHR (all p < 0.005). In IDEFICS-Germany, excess gain in BMI, FMI, and WtHR were predicted by a frequent consumption of nuts, meat, and pizza at baseline and a decrease in the consumption frequency of protein sources and snack carbohydrates during primary school years (all p < 0.01). The study confirms an adverse impact of fast food consumption on body composition during primary school years. Combinations of protein and carbohydrate sources deserve further investigation.

Network meta-analysis reaches nutrition research - Schwingshackl, Lukas; Buyken, Anette; Chaimani, Anna (European Journal of Nutrition)

Association between full breastfeeding, timing of complementary food introduction, and iron status in infancy in Germany: results of a secondary analysis of a randomized trial - Libuda, Lars; Hilbig, Annett; Berber-Al-Tawil, Seda; Kalhoff, Hermann; Kersting, Mathilde (European Journal of Nutrition)

The role of genetic variation of human metabolism for BMI, mental traits and mental disorders - Hebebrand, Johannes; Peters, Triinu; Schijven, Dick; Hebebrand, Moritz; Grasemann, Corinna; Winkler, Thomas W.; Heid, Iris M.; Antel, Jochen; Föcker, Manuel; Tegeler, Lisa; Brauner, Lena; Adan, Roger A.H.; et al. (Molecular Metabolism)

Effect of an vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients – a randomized controlled trial: study protocol - Föcker, Manuel; Antel, Jochen; Grasemann, Corinna; Führer, Dagmar; Timmesfeld, Nina; Öztürk, Dana; Peters, Triinu; Hinney, Anke; Hebebrand, Johannes; Libuda, Lars (BMC Psychiatry)

Do Android Taint Analysis Tools Keep their Promises? - Pauck, Felix; Bodden, Eric; Wehrheim, Heike (arXiv:1804.02903)
In recent years, researchers have developed a number of tools to conduct taint analysis of Android applications. While all the respective papers aim at providing a thorough empirical evaluation, comparability is hindered by varying or unclear evaluation targets. Sometimes, the apps used for evaluation are not precisely described. In other cases, authors use an established benchmark but cover it only partially. In yet other cases, the evaluations differ in terms of the data leaks searched for, or lack a ground truth to compare against. All those limitations make it impossible to truly compare the tools based on those published evaluations. We thus present ReproDroid, a framework allowing the accurate comparison of Android taint analysis tools. ReproDroid supports researchers in inferring the ground truth for data leaks in apps, in automatically applying tools to benchmarks, and in evaluating the obtained results. We use ReproDroid to comparatively evaluate on equal grounds the six prominent taint analysis tools Amandroid, DIALDroid, DidFail, DroidSafe, FlowDroid and IccTA. The results are largely positive although four tools violate some promises concerning features and accuracy. Finally, we contribute to the area of unbiased benchmarking with a new and improved version of the open test suite DroidBench.

Pattern based development of digital platforms - Drewel, Marvin; Gausemeier, Jürgen; Koldewey, Christian; Özcan, Leon (Proceedings of the 2018 ISPIM Connects)

Business Model Portfolio Planning for Smart Services - Koldewey, Christian; Echterfeld, Julian; Reilender, Meikel; Gausemeier, Jürgen (Proceedings of the ISPIM connects)

Steigerung der Intelligenz mechatronischer Systeme - Gausemeier, Jürgen; Trächtler, Ansgar

Consumer Responses to Paid Search - Empirical Evidence from a Bricks-and-Mortar Retailer - Schlangenotto, Darius

Vorausschau und Technologieplanung - Gausemeier, Jürgen; Bauer, Wilhelm; Dumitrescu, Roman

Strategische kompetenzorientierte Ausrichtung der Wertschöpfungsstruktur aus Perspektive der Produktion - Altemeier, Björn; Gausemeier, Pia; Sickmann, Sebastian; Frank, Maximilian (Vorausschau und Technologieplanung, Symposium für Vorausschau und Technologieplanung, Band 385)
Die Umgestaltung einer Lagerproduktion zur kundenauftragsorientierten Produktion ist das definierte strategische Ziel des Produktionsbereichs Professional bei Miele & Cie. in Bielefeld. In Bielefeld werden Geräte der Spül- und Medizintechnik mit sehr hoher Wertschöpfungstiefe und in kleinen Stückzahlen produziert. Die Tendenz zur weiteren Verkleinerung der Los- und Auftragsgrößen ist jedoch steigend. Daher sind Produktivitätssteigerungen in diesem Umfeld nur durch eine kontinuierliche Reduzierung der Durchlaufzeit möglich. Dies bedingt eine Verbes-serung der Anlagen- und Personalflexibilität, der Stabilität der Teileversorgung und der Qualität der produzierten Bauteile und Endgeräte. Neben den hohen Qualitätsanforderungen an Miele Produkte führt im Bereich Professional zusätzlich das Medizinproduktegesetz zu einer hohen Komplexität der gefertigten Produkte. Deshalb kommt der Kompetenz der Mitarbeiter in der Produktion eine zentrale Rolle zu. Die Betrachtung des gesamten Wertstroms vom Lieferanten bis zum Kunden ist bei der strategischen kompetenzorientierten Ausrichtung der Wertschöpfungsstruktur unerlässlich. Deshalb wurde im ersten Schritt die Ist-Situation der Wertschöpfungsstruktur und der eingesetzten Technologien analysiert. Anschließend wurden die Technologien hinsichtlich ihrer strategischen Relevanz und der in der Professional Produktion vorhandenen Kompetenzen bewertet. Für hierdurch priorisierte Technologien wurden mögliche alternative Technologien ermittelt. Vor dem Hintergrund der Kompetenzplanung konnte letztlich entschieden werden, welche Technologien selbst eingesetzt und welche Produktionsschritte zu Lieferanten ausgelagert werden. Der Beitrag stellt sowohl die hierzu entwickelte Methode als auch die Ergebnisse aus der Validierung für die Ausrichtung der Professional Produktion in Bielefeld dar.